Board Certification in Cosmetic Surgery: An Analysis of Punitive Actions. Issue 3 (13th July 2022) - Gabrick, Kyle; Makhoul, Alan T.; Riccelli, Vincent; Perdikis, Galen; Janis, Jeffrey E.; Drolet, Brian C.
Abstract : Background: American Board of Plastic Surgery (ABPS) diplomates complete training in aesthetic surgery through an Accreditation Council of Graduate Medical Education–accredited program. American Board of Cosmetic Surgery (ABCS) diplomates complete residency training in a "related" specialty, some historically nonsurgical, followed by an American Association of Cosmetic Surgery fellowship. Unlike the ABPS, the ABCS is not recognized by the American Board of Medical Specialties as an equivalent certifying board. This study evaluated differences in the rates of punitive action against diplomates of the ABPS and the ABCS. Methods: Diplomates were accessed from their respective society's websites. Punitive action data were obtained by search of publicly available state medical board databases. A comparative analysis was performed between ABPS and ABCS. Results: One thousand two hundred eight physicians were identified for comparative analysis. Two hundred sixty-six (22 percent) were members of the American Society of Plastic Surgeons, and 549 (49 percent) were members of The Aesthetic Society. ABCS diplomates had significantly higher rates of disciplinary administrative action by their respective state medical boards [ n = 31 (9.0 percent)] when compared with ABPS members [The Aesthetic Society, n = 26 (4.4 percent); ABPS, n = 8 (3.1 percent); p = 0.003], with a higher proportion of repeat offenders. In addition, ABCS diplomates had more public letters of reprimand [ABCS, n = 12 (3.5 percent); The Aesthetic Society, n = 6 (1.2 percent); and ABPS, n = 2 (0.8 percent); p = 0.015]. Conclusions: ABCS diplomates have significantly higher rates of punitive actions than ABPS diplomates. Although the reasons for this discrepancy warrant further investigation, punitive data should be transparently and publicly available to aid patients in informed decision-making.